India Power Sector Diagnostic Review : More Power to India - The Challenge of Distribution - World Bank (Washington, DC, 2014)
This report reviews the evolution of the Indian power sector since the landmark Electricity Act of 2003 (EA 2003, or EA), with a focus on distribution as key to performance and viability of the sector. While all three segments of the power sector generation, transmission, and distribution are important, revenues originate with the customer at distribution, so subpar performance there hurts the entire value chain. Persistent operational and financial shortcomings in distribution have repeatedly led to central bailouts for the whole sector, even though power is a concurrent 1 subject under the Indian constitution and distribution is almost entirely under state control. Ominously, the recent sharp increase in private investment and market borrowing means power sector difficulties are more likely to spill over to lenders and affect the broader financial sector. Government-initiated reform efforts first focused on the generation and transmission segments, reflecting the urgent need for adding capacity and the complexity of issues to be addressed at the consumer interface. Consequently, distribution improvements have lagged, but it is now clear that they need to be a priority. This report thus analyzes the multiple sources of weakness in distribution and identifies the key challenges to improving performance in the short and medium term.